Perbedaan Proporsi Gangguan Depresi dan Gangguan Cemas Antara Mahasiswa Preklinik dan Klinik - Yoan Chou; Dharmady Agus; Dwi Jani Juliawati (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2017)
Background: Medical education is full of burden and pressure, so that medical students are prone to get depressive disorder and anxiety disorder. These have been proven by several researches conducted in the faculties of medicine from abroad as well as in Indonesia. Medical students, either preclinical or clinical, need to face many obstacles, but clinical students have more demands than preclinical students and they are directly responsible for patient safety. The more demands of the clinical students made them prone to have more depressive and anxiety disorder.Method: This research was conducted as a cross-sectional study on 200 students on Atma Jaya Medicine Faculty by choosing 100 pre-clinical and clinical students with simple random sampling. Data were collected with structured interviews by using MINI ICD-10 instrument to determine the depressive and anxiety disorder.Results: There were significant differences between the proportion of depressive disorder and anxiety disorder among preclinical and clinical students in FKUAJ 2015 (p = 0.044 and p = 0.048). The proportion of depressive disorder and anxiety disorder in clinical students are higher than preclinical students (29% vs. 17% and 38% vs. 25%).Conclusions: Clinical students are more prone to get depressive disorder 1,99 times and anxiety disorder 1,84 times than preclinical students FKUAJ year 2015